Eskalasi Usaha dan Penyuluhan Pemasaran Berbasis E-Commerce sebagai Representasi Program Wira Desa di Desa Sumowono (BERDAYA Indonesian Journal of Community Empowerment, 2022)
Escalation is an increase the business escalation of the product representing the Wira Desa program aims to increase sales value and expand e-commerce based markets. Wira Desa activity is located in Sumowono Village, Kaligesing District, Purworejo Regency, Central Java. The representative products of the Wira Desa program are besek crafts, the production of palm sugar, as well as traditional medicine for the dried Mahkota Dewa. The method of implementing the Wira Desa activity program consists of 6 stages. First, we conducted a site survey, then socialized the program, then formed an association, continued with marketing training, then purchased equipment and product marketing, and evaluated the program. Based on the research conducted, it was found that 54% of participants thought that Wira Desa activities were useful, then 67% of participants answered that Wira Desa activities were clear and easy to understand, 60% of participants felt the benefits of Wira Desa activities, and the last 53 % of participants were satisfied with this Wira Desa activity.